How to choose the right English language textbook? - Eva Reid; Elena Kováčiková (Problemy Wczesnej Edukacji)
The book market in Slovakia is overloaded with various language books offered by prestigious publishing houses. The “international” textbooks are rather very general, not paying attention to cultural and language peculiarities which are different for each country and culture. Modern teaching approaches call for cross-curricular relations and the content of teaching might differ in every country. National books have the advantage of including cultural and language specifics of the particular country, connect contents of various schools subjects and take into consideration the needs of “home” language teachers with the aim to improve and develop specifically the sides of language systems and skills that are particularly necessary for students of their country. The paper analyses three English language textbooks for third grade of primary schools. Two textbooks are form major international publishing houses and are the most popular in Slovakia. The third book is written by Slovak authors and is new to the market. The method of document analysis was used to compare contents of linguistic and cultural diversity and supporting development of intercultural awareness and intercultural communicative competences of pupils.